«Esistere così come dipingere». Deleuze con Burri (Itinera, 2023)
The article aims to establish a theoretical dialogue between the work of Alberto Burri, one of the most influential Italian artists of the 20th century, and the late aesthetics of Gilles Deleuze. By drawing on the concept of image outlined by Deleuze in The Exhausted (1992), Burri’s art is conceptualized as the unfolding of a dimension of pure sense that singularizes forms rather than identifying bodies and signs. This ontological “purity” comes from a deep engagement with matter, considered as a plurality of material potencies. In conclusion, the article proposes an original understanding of image as a pre-symbolic zone of ontological collapse.